A Study of Health Maintenance Protocols in Family Practice - Herbert, Carol P. (1985)
A series of color-coded health maintenance protocols for four age groupings were introduced into a community health centre. In a pilot study of the 16-49 year age range, levels of recording before introduction of the protocols were below 50% in all categories, except “blood pressure” “coping skills” and “sexuality/contraception”. After one year, it was not possible to assess changes in recording of screening maneuvers reliably due to the short study period and major changes in staffing that coincidentally occurred during the study period. Further studies should use stable solo practices and a much longer follow up period.